2015
DOI: 10.1097/mbc.0000000000000104
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment with para-aminomethylbenzoic acid for chronic disseminated intravascular coagulation associated with aortic dissection

Abstract: Chronic disseminated intravascular coagulation is a rare complication of aortic dissection. Surgical correction or low molecular weight heparin is treatment of choice, but for a severe bleeding problem due to excessive fibrinolysis, para-aminomethylbenzoic acid would be a simple and effective therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Under these circumstances, blood component therapy (e.g., FFP and PC) is recommended to supplement the coagulation factors and platelets that have been consumed [ 9 ]. Several medical strategies have shown effectiveness in controlling DIC due to aortic dissection, including anticoagulation [ 6 , 14 , 15 ], antifibrinolytics [ 8 , 16 , 17 ], and a combination of both [ 11 , 18 , 19 ]. Although anticoagulation is not usually recommended for patients with severe DIC-associated bleeding [ 9 ] because it may cause bleeding complications elsewhere, some reports have shown the effectiveness and safety of anticoagulation treatment for DIC in patients with aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these circumstances, blood component therapy (e.g., FFP and PC) is recommended to supplement the coagulation factors and platelets that have been consumed [ 9 ]. Several medical strategies have shown effectiveness in controlling DIC due to aortic dissection, including anticoagulation [ 6 , 14 , 15 ], antifibrinolytics [ 8 , 16 , 17 ], and a combination of both [ 11 , 18 , 19 ]. Although anticoagulation is not usually recommended for patients with severe DIC-associated bleeding [ 9 ] because it may cause bleeding complications elsewhere, some reports have shown the effectiveness and safety of anticoagulation treatment for DIC in patients with aortic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Antifibrinolytics can promote the formation of false lumen thrombosis and terminate the consumption of coagulation factors once the false lumen is completely thrombosed [ 9 ]. Because of concern regarding obvious hemorrhagic diathesis, some researchers have treated DIC by combining blood components with antifibrinolytics (e.g., tranexamic acid and para-aminomethylbenzoic acid) and avoiding anticoagulation [ 8 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The course of this patient suggested that the administration of edoxaban is useful for DIC due to aortic dissection without severe adverse events. Previous reports of DIC caused by vascular disease have described the effectiveness of rTM ( 6 - 9 ), low-molecular-weight heparin (LMWH) ( 10 - 13 ), nafamostat mesylate ( 14 ), and para-aminomethylbenzoic acid (PAMBA) ( 15 ). However, the intravenous administration of these drugs places a considerable burden on patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the right renal artery is only involved, if there is the substantial circumferential extension of the AAD [ 3 - 4 ]. From our review, the diagnosis of several patients was extremely delayed, often until hemodynamic stability is compromised (Table 1 ) [ 5 - 10 ].…”
Section: Discussionmentioning
confidence: 99%